The Use of Past Tense in Research Method Chapter of English Education Students’ Thesis - Siti Zumrotus Sa’diyah (PGRI Provinsi Jawa Timur, 2022)
Error analysis is an important area of second and foreign language learning. This research aimed to describe the types of error based on surface strategy taxonomy and causes of error on the use past tense in research method chapter in English students’ thesis. This research used the descriptive qualitative method to identify one or a few variables that intended to use in this research design. The data were taken from 5 English education students’ thesis of STKIP PGRI Sidoarjo in year 2018 with the random sample. The research found errors result in the form of percentage were 18 or 16,5% errors found in omission, 21 or 19,3% errors found in addition, 69 or 63,3% errors found in misformation, and 1 or 0,9% errors found in misordering. Besides, the result found from the total causes of errors in the form of percentage were 75 or 96,2% causes of errors in overgeneralization, 0 or 0% causes of errors in neglecting the constraints of rules, 2 or 2,5% causes of errors in application of incomplete rules, and 1 or 1,3% causes of errors in hypothesis of the wrong concept. In conclusion, error analysis helped to know the students’ ability in understanding language learning, especially in writing research method chapter of thesis.